(untitled) (Progressive Agriculture, 2013)
The experiment was conducted with mature embryos of an aromatic rice variety (Basmati 370) to investigate the appropriate growth condition for callus induction as well as plant regeneration. Different concentrations of 2,4-D (0.0, 1.5, 2.5, 3.5, 4.5 mgL-1) in MS medium were used for callus induction. Among the concentrations of 2,4-D, 2.5 mg-1 was the best concentration for callus induction (95.83%). Different concentrations of Kinetin (0.0, 8.0, 10.0, 12.0, 14.0 mgL-1) with a constant concentration of NAA (0.5 mg-1) were used for plant regeneration from callus. The combination of 10.0 mg-1 Kinetin and 0.5 mg-1 NAA was found to be the best for shoot regeneration (77.50%). Different concentrations of MET (1.5, 2.5, 3.5 mg-1) in MS medium with a constant concentration of NAA (0.5 mg-1) were used for root induction. A combination of 2.5 mg-1 MET and 0.5 mg-1 NAA was found most efficient for root induction (85.00%) with higher number of roots per plant (19.50) and better root elongation (1.88 cm). The plantlet was survived well in the plastic pot as well in the earthen pot or in the field. DOI: http://dx.doi.org/10.3329/pa.v19i2.16921 Progress. Agric. 19(2): 45 - 50, 2008